2021
DOI: 10.1186/s40779-020-00295-z
|View full text |Cite
|
Sign up to set email alerts
|

Expert consensus on the prevention, diagnosis and treatment of cold injury in China, 2020

Abstract: Cold injury refers to local or systemic injury caused by a rapid, massive loss of body heat in a cold environment. The incidence of cold injury is high. However, the current situation regarding the diagnosis and treatment of cold injury in our country is not ideal. To standardize and improve the level of clinical diagnosis and treatment of cold injury in China, it is necessary to make a consensus that is practical and adapted to the conditions in China. We used the latest population-level epidemiological and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Bronchiolitis is still regarded as one of the most common diseases in children aged under 2 years-in particular, in infants less than 6 months of age-causing the heaviest psychological and economic burden on families in the world (6,10). More than 15% of bronchiolitis cases are severe, and this is even higher in developing countries (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bronchiolitis is still regarded as one of the most common diseases in children aged under 2 years-in particular, in infants less than 6 months of age-causing the heaviest psychological and economic burden on families in the world (6,10). More than 15% of bronchiolitis cases are severe, and this is even higher in developing countries (11).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that nCPAP was effective in overcoming intrinsic PEEP, reducing airway resistance, reducing airway collapse (especially terminal airways), reducing CO 2 retention, relieving respiratory muscle fatigue, as well as improving ventilation-blood flow ratio (6,12). nCPAP is conducted in children with spontaneous breathing as it is more consistent with the normal breathing cycle than invasive ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they can disturb the blood circulation, cause damage to the nerves, and give rise to a lifelong intolerance of cold and pain, not to mention the greater risk of re-injury in the same place. There is the additional risk that re-injury in the same place will be more serious the second time around [ 12 ]. Thus, NFCIs and FCIs can potentially reduce the sufferer’s quality of life and adversely affect the person’s career in the Armed Forces.…”
Section: Introductionmentioning
confidence: 99%
“…Frost injuries and illnesses usually affect military personnel, athletes involved in winter sports, residents of the northern regions, reindeer herders, etc. Today, despite the development of modern methods of invasive and functional diagnostics, the issues of determining the degree and predicting the outcome of a frostbite in the early periods of injury still remain controversial [1,2]. It is not difficult to diagnose systemic cold injury based on core body temperature or the patient's state of consciousness.…”
Section: Introductionmentioning
confidence: 99%